2016
DOI: 10.1080/00028487.2016.1201003
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Phylogeographic Structure of Coho Salmon in California

Abstract: Evaluation of population genetic structure and variation is an important part of planning for the recovery and management of protected species. Data from 18 polymorphic microsatellite DNA markers were used to analyze the phylogeographic structure of protected Coho Salmon Oncorhynchus kisutch from populations throughout California. Fish from 30 locations in two evolutionarily significant units (ESUs) representing most of the extant populations in the state were studied. Multiple analyses indicated a hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…These results indicate that genetic variation mirrors geography for Coho salmon, similar to human populations (Menozzi et al, 1978;Novembre et al, 2008). As previously observed, some Californian samples displayed high genetic diversity while others displayed reduced diversity, strongly suggesting recent population declines in some of these rivers (Rougemont et al, 2020;Gilbert-Horvath et al, 2016;Williams et al, 2011). Accordingly, highest levels of genetic diversity and lower β ST were observed in Cascadia, rather than California, as already noted (Rougemont et al, 2020).…”
Section: Genetic Variation Mirrors Geography and Reveal Fine Scale Ho...supporting
confidence: 78%
“…These results indicate that genetic variation mirrors geography for Coho salmon, similar to human populations (Menozzi et al, 1978;Novembre et al, 2008). As previously observed, some Californian samples displayed high genetic diversity while others displayed reduced diversity, strongly suggesting recent population declines in some of these rivers (Rougemont et al, 2020;Gilbert-Horvath et al, 2016;Williams et al, 2011). Accordingly, highest levels of genetic diversity and lower β ST were observed in Cascadia, rather than California, as already noted (Rougemont et al, 2020).…”
Section: Genetic Variation Mirrors Geography and Reveal Fine Scale Ho...supporting
confidence: 78%
“…All regions differed significantly in their distribution of singleton (p < 0.0001) except the comparison between Thompson and California ( S3 Fig ) The observed signal in the Thompson was consistent with our above observations of reduced diversity. Similarly, we hypothesized that such reduced number of singletons in a few Californian samples reflects recent and strong population declines in some of these populations [ 44 , 45 ] (see also S1 Text ). The similarity of the singleton distributions for both Cascadia and Alaska further emphasized the need for additional analyses (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The high number of ND2 haplotypes within the Coquille watershed, and the observation of shared haplotypes between the Coquille watershed and the Klamath and Nestucca watersheds agrees with previous studies demonstrating higher within‐population genetic variation than between populations (Ford et al, 2004 ; Olsen et al, 2003 ). In contrast, the Nestucca and Coquille O. kisutch populations belong to a different evolutionarily significant unit than the Klamath population (Lawson et al, 2007 ), and the Klamath population has been shown to belong to a lineage distinct from other California populations (Gilbert‐Horvath et al, 2016 ). The pattern of haplotypes observed here may imply migration from the Coquille watershed to the Klamath and Nestucca watersheds, and the Coquille watershed has been classified as a “functionally independent population” by Lawson et al ( 2007 ), meaning migration from other populations does not substantially affect it and it is a net donor to small populations (Lawson et al, 2007 , p. 10).…”
Section: Discussionmentioning
confidence: 99%